Determination of embryotoxic and teratogenic effects of flunixin meglumine given early stage in ovo - Murat Öznurlu; Yasemin Öznurlu (Eurasian Journal of Veterinary Sciences)
Aim: The aim of this study was to determine embryotoxic and teratogenic effects of flunixin meglumine (FM), a nonsteroid anti-inflammatory drug used for analgesic and antipyretic, given early stage in ovo. Material and Methods: For this purpose, 300 chicken eggs were used. The eggs were divided into the groups as follows: 1. Group: Control group, 2. Group: 2.2 mg/kg FM group, 3. Group: 5.5 mg/kg FM group and 4 Group: 11 mg/kg FM group. Test solutions were injected via air-sac just prior to the settlement of the eggs into the incubator. Eggs from each group were opened on various days of the incubation and developmental stages of embryos were determined according to the Hamburger-Hamilton scale. Also, malformation types, both live and relative embryo weights and crown-rump lengths (CRL) were determined. Results: The mortality in the treated FM groups was found to be significantly (P<0.05) higher than control. The live and relative embryo weights and embryo CRL values of the FM groups were significantly lower than that of the control group (P<0.05). In the treated FM groups showed embryonic growth retardation and various structural abnormalities. It may be stated administration of FM cause teratogenity in mammalian species when administered in pregnancy period.